202k views
1 vote
Given f(x) = x squared - 1 and g(x) = x+ 2, what is the value of h(-2) where h(x) = f(g(x))?

User Mud
by
4.9k points

1 Answer

2 votes

Answer:
h(-2)=-1

Explanation:

We need to find
f(g(x)). Substitute the function
g(x) into the function
f(x):


f(g(x)) = (x+ 2)^2- 1

Now, we know that the function
h(x) is
h(x)=f(g(x)), then:


h(x)=(x+ 2)^2- 1

In order to find the value of
h(-2), we must substitute
x=-2 into the function
h(x)=(x+ 2)^2- 1.

Therefore, the value of
h(-2) is:


h(x)=(x+ 2)^2- 1\\\\h(-2)=(-2+ 2)^2- 1\\\\h(-2)=(0)^2- 1\\\\h(-2)=0-1\\\\h(-2)=-1

User Naaman
by
5.2k points